Notch and NF-κB: Coach and Players of Regulatory T-Cell Response in Cancer - Ferrandino, Francesca; Grazioli, Paola; Bellavia, Diana; Campese, Antonio Francesco; Screpanti, Isabella; Felli, Maria Pia (Frontiers in Immunology, 2018)
The Notch signaling pathway plays multiple roles in driving T cell fate decisions, proliferation and aberrant growth. NF-κB is a cell-context key player interconnected with Notch signalling either in physiological and in pathological conditions. This review focuses on how multilayered cross-talk between different Notches and NF-κB subunits may converge on Foxp3 gene regulation and orchestrates CD4+ regulatory T (Treg) cells function in particular in the tumor microenvironment. Notably, Treg cells may play a pivotal role in the inhibition of anti-tumor immune responses, possibly promoting tumor growth. A future challenge is represented by further dissection of both Notch and NF-κB pathways and consequences of their intersection. This may shed light on the molecular mechanisms regulating Treg cell expansion and migration to peripheral lymphoid organs thought to facilitate tumor development and still to be explored. In so doing, new opportunities for combined and/or selective therapeutic approaches to improve anti-cancer immunity may be found.